2018
DOI: 10.1017/s0140525x18000948
|View full text |Cite
|
Sign up to set email alerts
|

How foraging works: Uncertainty magnifies food-seeking motivation

Abstract: Food uncertainty has the effect of invigorating food-related responses. Psychologists have noted that mammals and birds respond more to a conditioned stimulus that unreliably predicts food delivery, and ecologists have shown that animals (especially small passerines) consume and/or hoard more food and can get fatter when access to that resource is unpredictable. Are these phenomena related? We think they are. Psychologists have proposed several mechanistic interpretations, while ecologists have suggested a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 233 publications
1
58
1
Order By: Relevance
“…More precisely, the finding that 50% reward availability enhances retention as compared with 100% is consistent with extensive animal and human studies, a finding argued to be mediated by the subjective value assigned to rewards during acquisition of novel goal‐directed behaviors (for recent reviews, see Refs. ). In support, neurophysiological lines of evidence suggest that the subjective valuation of rewards is dynamically modulated as acquisition proceeds, influencing reward‐related DAergic signaling.…”
Section: Discussionmentioning
confidence: 97%
“…More precisely, the finding that 50% reward availability enhances retention as compared with 100% is consistent with extensive animal and human studies, a finding argued to be mediated by the subjective value assigned to rewards during acquisition of novel goal‐directed behaviors (for recent reviews, see Refs. ). In support, neurophysiological lines of evidence suggest that the subjective valuation of rewards is dynamically modulated as acquisition proceeds, influencing reward‐related DAergic signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Anselme & Gurturkun [104], in a recent paper shows that "uncertainty" magnifies food searching behavior in birds which then increases exploration and survival. This "uncertainty principle" could equally be applied in communication to reduce potentially emotionally inflammatory situations, encourage group cohesion which in turn will encourage social exploration and curiosity, leading to the acquisition of more environmental and social knowledge.…”
Section: "Uncertainty" Behaviours Indicative Of Approach Avoidance Cmentioning
confidence: 99%
“…A recent review of animal research by Anselme and Güntürkün (2018) showed that in environments marked by uncertainty about food, animals shifted toward conservation strategies, including caching and hoarding food, eating more, and gaining weight. Thus, uncertainty causes conservation of energy resources even in quite simple animals.…”
Section: Introductionmentioning
confidence: 99%
“…A complete list of the mediators and moderators tested in these studies is presented in the Supplementary Materials . The revised theory, that uncertainty serves as a cue to stimulate conservation, has emerged as a more plausible alternative, particularly in light of the recent review by Anselme and Güntürkün (2018) .…”
Section: Introductionmentioning
confidence: 99%